2013
DOI: 10.1007/s13277-013-1420-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between ERCC1 C8092A and ERCC2 K751Q polymorphisms and risk of adult glioma: a meta-analysis

Abstract: While the ERCC1 C8092A and ERCC2 K751Q polymorphisms have received much attention for their potential associations with adult glioma risk, inferences from such studies are hindered by their limited statistical power and conflicting results. The aim of this meta-analysis is to provide a relatively comprehensive account of the association between these two polymorphisms and adult glioma risk. A literature search for eligible studies published before September 1, 2013 was conducted in PubMed, Embase, Web of Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In an earlier quantitative assessment looking at the relationship of rs13181 and rs3212986 to adult glioma, Xu et al found an elevated risk among subjects of Asian ancestry attributable to the former polymorphism and a similar increase for the latter polymorphism [44]. Almost at the same time, Yuan et al associated rs11615 and rs3212986 with glioma and observed a main effect particularly in Asian [45].…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier quantitative assessment looking at the relationship of rs13181 and rs3212986 to adult glioma, Xu et al found an elevated risk among subjects of Asian ancestry attributable to the former polymorphism and a similar increase for the latter polymorphism [44]. Almost at the same time, Yuan et al associated rs11615 and rs3212986 with glioma and observed a main effect particularly in Asian [45].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Yuan et al suggested that common variants in ERCC1 may contribute to susceptibility to glioma, especially in Asians [ 24 ]. The AA genotype of ERCC1 C8092A might be associated with a higher risk of adult glioma than the CA and CC genotypes and that the risk allele of ERCC2 K751Q confered a significant susceptibility to adult glioma, especially in Asian populations [ 25 ]. Strong evidence for the association between XRCC3 C18607T polymorphism and glioma risk was found in a meta-analysis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA variants in MLH1 , which is involved in mismatch repair systems, are known to cause the hereditary cancer disorder ‘Lynch syndrome’ and also confer susceptibility to azoospermia and oligozoospermia (58, 59). Interestingly, an identical mutation C8092A (rs3212986) in the DNA base excision repair gene ERCC1 has independently been linked to both idiopathic azoospermia (60) and various types of cancer, including breast carcinoma, head and neck carcinoma and adult glioma (6163). No studies have performed a mutational screening of these genes in male infertility cases with cancer as a comorbid state.…”
Section: Heritable Susceptibility To Cancer and Male Infertilitymentioning
confidence: 99%